2013
DOI: 10.1038/eye.2013.195
|View full text |Cite
|
Sign up to set email alerts
|

Refractive errors in a rural Korean adult population: the Namil Study

Abstract: Purpose To assess the prevalence of refractive errors, including myopia, high myopia, hyperopia, astigmatism, and anisometropia, in rural adult Koreans. Methods We identified 2027 residents aged 40 years or older in Namil-myeon, a rural town in central South Korea. Of 1928 eligible residents, 1532 subjects (79.5%) participated. Each subject underwent screening examinations including autorefractometry, corneal curvature measurement, and best-corrected visual acuity. Results Data from 1215 phakic right eyes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 14 publications
6
28
1
Order By: Relevance
“…In this study, the prevalence of myopia was nearly the same as those in urban areas of China, while the prevalence of HM was similar to that reported in rural areas of other Asian countries. In South Korea, the prevalence of myopia and HM was 20.5% and 1.0%, respectively, among adults above 40 years in the Namil Study [74]. Relatively low prevalence in the study was reflected by rural lesions, it was similar to that of rural Chinese population.…”
Section: East Asian Countriesmentioning
confidence: 55%
“…In this study, the prevalence of myopia was nearly the same as those in urban areas of China, while the prevalence of HM was similar to that reported in rural areas of other Asian countries. In South Korea, the prevalence of myopia and HM was 20.5% and 1.0%, respectively, among adults above 40 years in the Namil Study [74]. Relatively low prevalence in the study was reflected by rural lesions, it was similar to that of rural Chinese population.…”
Section: East Asian Countriesmentioning
confidence: 55%
“…Yoo et al 19 analyzed data from 1215 phakic right eyes, measuring non-cycloplegic refraction and corneal curvature with an autorefractometer. The mean astigmatic refractive error in the study sample was −0.98±0.77 D. In total, 63.7% and 34.8% of the patients had refractive astigmatism (RA) >−0.5 D and >−1.0 D, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…16 Both countries have a high prevalence of myopia. 34,35 This is in contrast with Western countries, where NTG is reported to comprise approximately 20% to 50% of the total glaucoma cases, and approximately 10% to 30% is associated with myopia. [36][37][38] Studies of Korean glaucoma patients revealed that the posterior sclera and the LC were thinner in NTG eyes compared to glaucomatous eyes with high IOP.…”
Section: Discussionmentioning
confidence: 99%